The Impact of Artificial Intelligence (AI) on Omnichannel Customer Experience - Damayanti, Rizki Wahyuning; Sumayyah, Sumayyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to determine the impact of Artificial Intelligence (AI) on Omnichannel Customer Experience (OCX). This research is quantitative with surveys as the data collection method. Data collection for this research was carried out on all Indonesian people. The data collection method uses an online questionnaire via Google Form which is obtained directly from the field and data collection is only carried out once and only represents at that time or cross- sectionally. The study collected data from 431 respondents in Indonesia. Hypothesis testing was performed using SEM-PLS with the SmartPLS software. The findings of this study suggest that dimension of AI can enhance the omnichannel customer experience.